PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE LEARNING CYCLE 5E TERHADAP KETERAMPILAN BERPIKIR KREATIF SISWA SMP NEGERI 2 KUANTAN MUDIK - Dehlia Katri Pineza; Supentri; Kingkel Panah Grosman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low level of creative thinking skills of students at SMP Negeri 2 Kuantan Mudik. This is caused by the old learning method which still uses the lecture method. The low level of creative thinking skills of students in the PPKn subject is indicated by the results of pre-research which show that students are less active in the learning process, students are less brave to express their opinions, less interact and collaborate with classmates in solving problems and teachers have not used varied learning models. Data collection was carried out using observation and questionnaire methods. This research was conducted on grade IX students of SMP Negeri 2 Kuantan Mudik consisting of 2 classes, namely class IX1 with 22 students and class IX2 with 23 students. Data analysis was carried out using the SPSS processing application after all data were tested for validity and reliability on the data. The results showed that the average control class experienced a not very significant increase, in the control pretest showed an average of 55.22 and there was an increase in the results to 58.04. This means that the usual learning method or lectures did not greatly influence students in creative thinking. Meanwhile, in the experimental class, there was a significant increase in the average score after the treatment. The pretest average was 53.95, and the posttest average increased significantly to 71.18. This average score indicates that the 5e learning cycle method has an impact on creative thinking skills.